The impact of the Sarbanes-Oxley Act on clients’ audit opinion shopping behavior - CHOI, Jong-Hag (Institutional Knowledge at Singapore Management University, 2016)
This study investigates whether the tendency for audit clients to engage in opinion shopping becomes weaker after the enforcement of the Sarbanes-Oxley Act (SOX). While Lennox (2000) provides evidence that U.K. firms successfully engage in opinion shopping, there is limited evidence on the mitigating effect of SOX on opinion shopping. Using observations collected from the period before and after the enforcement of SOX (year 2001, 2004 and 2005), we find that, for our sample period, firms are likely to switch (retain) their incumbent auditors when the likelihood of receiving a going concern opinion is lower (higher) from a successor auditor, suggesting evidence of opinion shopping. More importantly, we find that firms are less likely to engage in opinion shopping after the enforcement of SOX. These findings suggest that more stringent legal and audit environment in the post-SOX period, at least partially, restricts firms’ opportunistic behavior of shopping for a better audit opinion and enhances auditor independence. These findings provide valuable implications to regulators as well as academicians and practitioners.